Impact of manufacturers’ eco-design decisions on the closed-loop supply chain under recycling rate regulations - Wenxia Liu; Jiang Jiang; Zhixin Mao; Honglei Liu (PLoS ONE, 2025)
To address increasingly severe environmental issues, various countries have introduced relevant environmental protection regulations. This paper proposes a new government regulation measure to encourage manufacturers to improve recycling rates. Governments set recycling rate targets and reward-penalty mechanisms. This paper constructs a game model involving a manufacturer and a remanufacturer within a closed-loop supply chain system. It studies the equilibrium decisions in three scenarios: no government intervention, manufacturers not taking improvement measures despite government-set recycling rate targets, and manufacturers adopting ecological design after such targets are established. Results indicate that after governments establish recycling rate target: (1) After manufacturers adopt ecological design, the prices of new and remanufactured products decrease, sales volume increases, and the profits of both manufacturers and remanufacturers rise. Therefore, manufacturers would be well-advised to adopt eco-design strategies to enhance the level of recycling. (2) As the recycling rate target increase, the level of ecological design decreases, and the prices of new and remanufactured products rise. It is recommended that governments initially set lower recycling rate targets and then gradually increase them. (3) With the increase in the reward-penalty coefficient, the level of ecological design rises, and the price of new products first increases and then decreases. When remanufacturing is unrestricted, the prices of remanufactured products decrease; however, when remanufacturing is restricted, the prices of remanufactured products first increase and then decrease. Therefore, governments would be well-advised to establish a relatively high reward-penalty coefficient.